Stearic acid attenuates profibrotic signalling in idiopathic pulmonary fibrosis. Issue 3 (6th October 2020) - Kim, Hak‐Su; Yoo, Hyun Ju; Lee, Kwang Min; Song, Ha Eun; Kim, Su Jung; Lee, Jae Ok; Hwang, Jung Jin; Song, Jin Woo
ABSTRACT: Background and objective: Lipid metabolism dysregulation has been implicated in the pathogenesis of IPF; however, the roles of most lipid metabolites in lung fibrosis remain unexplored. Therefore, we aimed to identify changes in lipid metabolites in the lung tissues of IPF patients and determine their roles in pulmonary fibrosis. Methods: Free fatty acids in the lung tissues of IPF patients and controls were quantified using a metabolomic approach. The roles of free fatty acids in fibroblasts or epithelial cells treated with TGF‐β1 were evaluated using fibrotic markers. The antifibrotic role of stearic acid was also assessed in a bleomycin‐induced lung fibrosis mouse model. Protein levels in cell lysates or tissues were measured by western blotting. Results: The levels of stearic acid were lower in IPF lung tissues than in control lung tissues. Stearic acid significantly reduced TGF‐β1‐induced α‐SMA and collagen type 1 expression in MRC‐5 cells. Furthermore, stearic acid decreased the levels of p‐Smad2/3 and ROS in MRC‐5 cells treated with TGF‐β1 and disrupted TGF‐β1‐induced EMT in Beas‐2B cells. Stearic acid reduced the levels of bleomycin‐induced hydroxyproline in a mouse model. Conclusion: Changes in the free fatty acid profile, including low levels of stearic acid, were observed in IPF patients. Stearic acid may exert antifibrotic activity by regulating profibrotic signalling. Abstract : Stearic acid levels in IPF lung tissues were reduced compared with those in control lung tissues. Stearic acid alleviated pulmonary fibrosis in vitro by inhibiting TGF‐β1‐induced p‐Smad2/3. Stearic acid also showed antifibrotic effects in mice with bleomycin‐induced lung fibrosis. Taken together, stearic acid may be a therapeutic target for IPF. See related Editorial